Comparative study of frictional forces generated by NiTi archwire deformation in different orthodontic brackets: In vitro evaluation - Queiroz,Gilberto Vilanova (2012)
INTRODUCTION: The purpose of this study was to compare the frictional forces between 0.014-in NiTi wires (Aditek) with 4 mm horizontal deflection and brackets with different archwire ligation systems. METHODS: Four types of self-ligating brackets (Damon MX, Easy Clip, Smart Clip and In-Ovation), a triple bracket (Synergy) and a twin bracket with 8-shaped ligature (Tecnident) were tested. Twin brackets with conventional elastomeric ligatures (Morelli) were used as control group. Tests were repeated 10 times for each bracket/archwire combination. Frictional forces were measured in an Instron universal tensile machine at 3 mm/minute speed and a total displacement of 6 mm. Statistical analysis comprised ANOVA and Dunnett's multiple comparison post hoc test. RESULTS: Deflection-induced frictional (DIF) forces increased in the following order: Synergy, Damon, 8-shaped Ligature, Easy Clip, In-Ovation, Smart-Clip and conventional ligatures. The differences among groups were significant, with the exception of the 8-shaped ligature groups which was equal to the Damon and Easy Clip groups. CONCLUSIONS: Compared to conventional ligatures, all ligation systems tested reduced frictional forces. However, such reduction varied according to the ligation system employed.